Strengthening Civic Disposition Through Co-Curricular Education Program at Muhammadiyah Darul Falah Elementary School - Erwin Ardianzah; Joko Setiono; Darsinah Darsinah; Murfiah Dewi Wulandari (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
Basic education has a strategic role in shaping the civic disposition of students from an early age. Civic disposition includes an attitude of responsibility, social concern, tolerance, discipline, and commitment to the values of Pancasila and democratic life. Social challenges and global dynamics require schools not only to focus on the mastery of knowledge, but also on strengthening the affective and behavioral dimensions of students. This study aims to describe the implementation of co-curricular education programs in fostering and strengthening the civic character of students at SD Muhammadiyah Darul Falah, focusing on the form of co-curricular activities and the role of teachers and schools in the process of internalizing civic values. The research uses a descriptive qualitative approach. Data were obtained through observation, interviews, and documentation studies on the implementation of educational programs in schools. The validity of the data was tested through triangulation of sources and techniques, while the data analysis was carried out with the Miles and Huberman model which included data reduction, data presentation, and conclusion drawn. The results of the study show that cocurricular-based education programs, such as social care activities, community service, discipline habituation, and collaborative activities, contribute significantly to strengthening the attitude of responsibility, social concern, tolerance, active participation, and democratic attitude of students. The role of teachers as facilitators and role models, as well as consistent support of school culture, are key factors for the success of internalizing civic values. The findings of this study provide a theoretical contribution to the development of the study of civic education in elementary schools and practical benefits as a reference for the development of educational programs based on strengthening civic disposition in Muhammadiyah schools.